On the Solution of the Eigenvalue Assignment Problem for Discrete-Time Systems - El-Sayed M. E. Mostafa; Abdallah W. Aboutahoun; Fatma F. S. Omar (Journal of Applied Mathematics)
The output feedback eigenvalue assignment problem for discrete-time systems is considered. The problem is formulated first as an unconstrained minimization problem, where a three-term nonlinear conjugate gradient method is proposed to find a local solution. In addition, a cut to the objective function is included, yielding an inequality constrained minimization problem, where a logarithmic barrier method is proposed for finding the local solution. The conjugate gradient method is further extended to tackle the eigenvalue assignment problem for the two cases of decentralized control systems and control systems with time delay. The performance of the methods is illustrated through various test examples.